Which Hyperglycemic Model of Zebrafish (Danio rerio) Suites My Type 2 Diabetes Mellitus Research? A Scoring System for Available Methods - Salehpour, Aria; Rezaei, Mohammad; Khoradmehr, Arezoo; Tahamtani, Yaser; Tamadon, Amin (Frontiers in Cell and Developmental Biology, 2021)
Despite extensive studies on type 2 diabetes mellitus (T2DM), there is no definitive cure, drug or prevention. Therefore, for developing new therapeutics, proper study models of T2DM is necessary to conduct further preclinical researches. Diabetes has been induced in animals using chemical, genetic, hormonal, antibody, viral and surgical methods or a combination of them. Beside different approaches of diabetes induction, different animal species have been suggested. Although more than 85 percent of articles have proposed rat (genus Rattus) as the proper model for diabetes induction, zebrafish (Danio rerio) models of diabetes are being used more frequently in diabetes related studies. In this systematic review, we compare different aspects of available methods of inducing hyperglycemia referred as T2DM in zebrafish by utilizing a scoring system. Evaluating 26 approved models of T2DM in zebrafish, this scoring system may help researchers to compare different T2DM zebrafish models and select the best one regarding their own research theme. Eventually, glyoxalase1 (glo1–/–) knockout model of hyperglycemia achieved the highest score. In addition to assessment of hyperglycemic induction methods in zebrafish, eight most commonly proposed diabetic induction approval methods are suggested to help researchers confirm their subsequent proposed models.